Optimising Workforce Productivity: A Model for Organizational Excellence in Performance and Quality - Ahmad Yousef Areiqat; Tamara Mahmoud Rasheed Al-Qaruty (Migration Letters, 2023)
This part will discuss the significant marks of human asset efficiency for accomplishing authoritative greatness, zeroing in on advancement and quality. It is a spellbinding survey and blended research. The administration experts of Amman associations for assessment act as the populace for the pointer arrangement. Exploratory variable investigation and underlying condition demonstrating were used to look over the information; according to the section discoveries, the labour force efficiency of the board is essentially affected by EFQM and business. EFQM is likewise impacted in a critical and expanding way by business ventures. Thus, we can advance toward authoritative greatness by reinforcing the pointers affecting human asset efficiency and stressing quality and business venture. Accordingly, we can push toward authoritative greatness by supporting the pointers influencing enterprising business efficiency and emphasising quality and business venture.